Revision Study of Green Concrete - Saadoon, Ahmed Sagban; Abbas, Abdulnasser Mohammed; Almayah, Abdulamir Atalla (Basrah Journal for Engineering Sciences, 2019)
It is very crucial to minimize the environmental impact that induced from the development of industry, by applying strict policies and innovate eco-friendly industries. Indeed, construction manufacture considered as one of the most industries that affect the environment, especially concrete production and usage in structural buildings. For instance, traditional concrete, which is consists of a high amount of cement, is contributed to the emission of CO 2 . Therefore, researchers seeking to develop a new technology of concrete by replacement some amount of cement by materials which are considered to become more friendly to the environment. Nowadays, this new technology is known as Green Concrete. The importance of using green concrete is not only to decrease the emission amounts of CO 2 but also to replace cement by industrial waste. In this paper, a review has been presented to understand green concrete benefits and materials that may be used instead of cement and aggregate.